2022
DOI: 10.1002/adfm.202206653
|View full text |Cite
|
Sign up to set email alerts
|

Developing Thermoregulatory Hydrogel Electrolyte to Overcome Thermal Runaway in Zinc‐Ion Batteries

Abstract: Zinc‐ion batteries (ZIBs) that use water‐based electrolytes have attracted significant attention. However, under harsh conditions, extreme heat is accumulated inside ZIBs, which inevitably causes thermal runway risk. Therefore, the practical applications of rechargeable ZIBs are significantly limited because the internal heat accumulated by harsh conditions induces drastic bulges or even explosions. To overcome this limitation, a self‐adaptive thermoregulatory hydrogel electrolyte (TRHE) that integrates phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…64,75 In addition to crystallohydrate salts, researchers have explored the adsorption of organic PCMs such as PEG into polymer networks to prepare PCPCs for the thermal management of ESDs. Qian et al 76 proposed a hydrogel electrolyte in which PEG was integrated into agarose main chains via hydrogen bonding for the thermal management of ZIBs. The prepared PCPC exhibited a phase-change temperature of 59.70 1C and a phase-change enthalpy of 143.43 J g À1 (Fig.…”
Section: Phase-change Polymer Composites (Pcpcs)mentioning
confidence: 99%
See 3 more Smart Citations
“…64,75 In addition to crystallohydrate salts, researchers have explored the adsorption of organic PCMs such as PEG into polymer networks to prepare PCPCs for the thermal management of ESDs. Qian et al 76 proposed a hydrogel electrolyte in which PEG was integrated into agarose main chains via hydrogen bonding for the thermal management of ZIBs. The prepared PCPC exhibited a phase-change temperature of 59.70 1C and a phase-change enthalpy of 143.43 J g À1 (Fig.…”
Section: Phase-change Polymer Composites (Pcpcs)mentioning
confidence: 99%
“…Hydrogels and crosslinked polymers with a three-dimensional (3D) network structure are commonly used as functional polymeric backbones to supporting PCMs. [74][75][76] Novel 3D polymer networks supporting PCMs should be further explored for lithium metal batteries, on which few studies have been reported.…”
Section: Phase-change Polymer Composites (Pcpcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the reported PVA-ZnCl 2 hydrogel, [41] gelatin-PAM hierarchical polymer hydrogel, [42] PAAm/alginate-Zn hydrogel [37] and Zn(CF 3 SO 3 ) 2 -PVDF-HFP [34b] hydrogel electrolytes. They extend the electrochemical stable voltage (~3 V) greatly through decreasing the water solvent ratio and strengthening hydrogen bonding reaction between polymer and water molecules; contribute to the ordered diffusion of Zn 2 + and the uniform deposition of Zn through the Zn 2 + -confinement effect of polymer matrix; and finally improve the cycling stability (up to thousands of cycles) of the battery through suppressing side reactions on electrode and electrolyte sides [39,40] (as shown in Figure 3d, e). Various works where the polymer modification, biopolymers and functional additives addition are reported, which enriches the GPEs family significantly.…”
Section: Gel Polymer Electrolyte (Hydrogel Electrolyte)mentioning
confidence: 99%